Understanding Formative Assessment Practice in the EFL Exam-Oriented Context: An Application of the Theory of Planned Behavior - Zeng, Juan; Huang, Liyan (Frontiers in Psychology, 2021)
Formative assessment (FA) has been used to facilitate EFL learning and teaching. However, due to factors such as task complexity and time constraints, FA implementation faces a variety of challenges, especially in countries with an exam-oriented education system. This study examines the features of FA practice and explains their underlying aspects in the Chinese EFL context from a social psychology perspective. It adopts a mixed-methods research approach. Guided by the theory of planned behavior, 10 English teachers from Guangdong province in China were interviewed to establish an item pool for a structured questionnaire. A total of 161 English teachers from four cities in Guangdong province took part in the subsequent survey. The results revealed that English teachers in China have an implicit understanding of FA, based primarily on its literal meaning and their own teaching experience. They know and follow FA methods but lack confidence about their own practice. Regional differences were significant. Possible reasons for Chinese EFL teachers’ perceptions and practice are the teachers’ own attitudes, the influence of other stakeholders, and the limitations of the FA methods. The study elucidates the features of FA practice and its mechanism in an EFL exam-oriented context.mechanism in an EFL exam-oriented context.